Development and validation of standardless and standards-based X-ray microanalysis. Issue 1 (July 2020) - Pinard, P T; Protheroe, A; Holland, J; Burgess, S; Statham, P J
Abstract: We describe one approach to standardless quantification for energy-dispersive (ED) X-ray spectrometry that can achieved unnormalised results with an accuracy better than 5 %. This approach relies on a "factory" standards database, a model of the detector efficiency, calculated peak profiles, and a multi-step process to correct spectral artefacts and extract X-ray intensities from ED spectra. These processes and components, as well as the underlying equations involved in the quantification are detailed to illustrate the similarities between this approach and the classical standard-based k -ratio quantification. The accuracy was assessed by measuring and quantifying standard samples at different accelerating voltages (15 and 20 kV) and input count rates (50 and 200 kcps). In all cases, the measured, unnormalised concentrations yielded a centred distribution with a relative error less than 5 %. Excluding the analysis of light elements (B, C, O, N, F) improved the relative error to around 2 %